(untitled) (ModaPalavra e-periódico, 2010)
Nurses who participated in the Second World War wrote an important chapter to the history of women and nursing. This paper aims to address this story from the perspective of education and fashion. Through the stories and photographs available in the literature and in the collections of the press, we built a career in nursing from the viewpoint of uniform. In the analysis, the styles relate to the steps of the route of the nurses, determining the values, concepts, behaviors transmitted by their intermediates. Thus, we created a historical wardrobe, with the main styles of uniforms in the years of war.